TEACHER EDUCATION FOR SINGLE-GRADE TEACHING DISQUALIFIES MULTI-GRADE TEACHING FOR RURAL EDUCATION: Received: 13th September 2021; Revised: 19th January 2022, 30th March 2022; Accepted: 02nd April 2022 - Mpahla, Ntando; Makena, Bulelwa (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This paper examined the collision of teacher education for single-grade teacher classroom practices with multi-grade classroom teaching. Teachers educated for the normal situation of single-grade classroom teaching are not linked to the competencies required to practice and teach multi-grade classrooms. Of the current models of teacher education, none pays attention to the multi-grade teaching of rural education but only focuses on monograde classroom teaching. The paper used a qualitative research methodology. The researchers felt it vital to use a qualitative approach as the paper studies the life experiences of teachers in their natural and context-specific settings. Participants were selected through purposive sampling because of their common defining characteristics in the problem under study. Data collection came through semi-structured interviews and observation. When analysing data, a narrative analysis was used. The results of this paper indicated that the current crop of teachers in multi-grade schools does not possess the pedagogical knowledge required. This finding concludes that teachers have no specialised knowledge that would improve learner outcomes from the quality of teaching workforce and the quality of teaching.